If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2y + -1) = 18 Reorder the terms: 6(-1 + 2y) = 18 (-1 * 6 + 2y * 6) = 18 (-6 + 12y) = 18 Solving -6 + 12y = 18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 12y = 18 + 6 Combine like terms: -6 + 6 = 0 0 + 12y = 18 + 6 12y = 18 + 6 Combine like terms: 18 + 6 = 24 12y = 24 Divide each side by '12'. y = 2 Simplifying y = 2
| 2(a+4)2*126=0 | | 17x-3(4+5x)=60 | | 7x+3-2x=32 | | 3(a-8)=42 | | Sin(0.5x)=0 | | 14+9n-5n=39 | | 5(2n+4)=50 | | 13+6d=67 | | 3(9-3x-4x)+8(3x+4)=11 | | 7(5x-4)=11(2x+1) | | 3a+4a+5=75 | | -51+2x+5x=26 | | 2=6x+1-81-y | | Solve(x-8)(3x+5)=0 | | 2y=-3x-5 | | 14=10-1/4m | | (25x-2)+(25x+1)+(20x-1)=278 | | 3(2x+2)=6(1+8x) | | (y+1)=2(x-3) | | 9c-15=4c | | 8(4x+1)=9(5x-2) | | 10x^9-17x^7+7x^6= | | 5x-1/2x=18 | | 5(x-90)-4(x+150)=950 | | x+x/2+4=30 | | 8(d+5)=23 | | 4x^2+8-12=0 | | n^2+8=-6n | | 3(7+c)=60 | | 52000-8n=18000+8n | | 8(4x+1)=14(2x-3) | | [3(m-5)+16]-[2(3m-3)+5]= |